Design And Development Of A Ticket Booking Application Using Extreme Programming At Serayu Larangan - Rifkiansyah, Hanif; Azrino Gustalika*, Muhamad (Kresnamedia Publisher, 2025)
This research was conducted with the aim of developing a web-based tourist ticket booking service application system using the Extreme Programming (XP) development method that is able to facilitate the ticket transaction process both from the side of online buyers and tour managers at the counter. Serayu Larangan Tourism Village, Mrebet District, Purbalingga Regency has promising tourism potential. However, there is still no application that can support the running of the tourism business, such as in the process of selling and recording tickets. Therefore, a system is needed that can facilitate the management of the ticket sales and booking process and data collection of sales reports. This research begins with data collection carried out through the stages of observation, interviews, and literature studies. After the data is collected, system development is carried out using the Extreme Programming (XP) method which consists of four main stages which include planning, design, coding, and testing. From the results of system testing using the Black Box method for ten user features and fifteen admin features showed a 100% success rate. Then the results obtained from the User Acceptence Test (UAT) conducted by ten respondents showed an average percentage of acceptance rate of 87.6%.